2015
DOI: 10.1021/acsami.5b02402
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Titanium Drug Eluting Platforms Based on a Poly-β-cyclodextrin–Chitosan Layer-by-Layer Self-Assembly Targeting Infections

Abstract: In the field of implantable titanium-based biomaterials, infections and inflammations are the most common forms of postoperative complications. The controlled local delivery of therapeutics from implants through polyelectrolyte multilayers (PEMs) has recently emerged as a versatile technique that has shown great promise in the transformation of a classical medical implant into a drug delivery system. Herein, we report the design and the elaboration of new biodegradable multidrug-eluting titanium platforms base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 64 publications
1
55
0
1
Order By: Relevance
“…The layer-by-layer coating platform is a promising technique for local drug delivery [32, 33]. Several studies demonstrated new implant coating strategies using LBL coating targeting infection and bone formation [34, 35], but few studies have used this method to mitigate peri-prosthetic inflammation and osteolysis directly. We have recently developed a layer-by-layer coating platform on implant surfaces that demonstrates controlled release of 7ND protein with retained biological activity in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…The layer-by-layer coating platform is a promising technique for local drug delivery [32, 33]. Several studies demonstrated new implant coating strategies using LBL coating targeting infection and bone formation [34, 35], but few studies have used this method to mitigate peri-prosthetic inflammation and osteolysis directly. We have recently developed a layer-by-layer coating platform on implant surfaces that demonstrates controlled release of 7ND protein with retained biological activity in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular research interest are antibiotic eluting polymer coatings which hold great clinical translational potential. However, the drug loading efficiency is limited and duration of antibiotic release from commonly available polymer coatings is several hours to a few days [52,53]. In fact, constant aseptic condition is critical for normal osseous functions in the early healing stage (3 months).…”
Section: Discussionmentioning
confidence: 99%
“…Following this approach, polydopamine and other catecholamines have been modified with various fouling resistant materials and antimicrobial compounds to prevent biofouling of the surfaces . These include hydrophilic antifouling polymers, zwitterionic amino acids, bioinspired antimicrobial compounds, lysing and disinfecting agents, silver nanoparticles, combinations of silver nanoparticles and antifouling polymers, bactericidal enzymes, and the attachment of multidrug eluting polyelectrolyte multilayer coatings …”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%